Institutional diagnostics of climate adaptation - Christoph Oberlack (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2014)
Institutions are one of the decisive factors for climate adaptation. Nevertheless, current understanding of the institutions-adaptation-nexus is fragmented across the scientific community; is often theoretically ad-hoc or eclectic and at times contradictory. Moreover, knowledge claims are typically raised either for specific cases or overly generic, whereas a diagnostic method may be most effective for cross-case learning about institutional deficits and success factors in climate adaptation. This study develops an institutional diagnostics approach to climate adaptation by means of a systematic meta-analysis of 52 studies comprising 120 cases from Europe. The results show that maladaptation, adaptation barriers and limits are rooted in institutional deficits that can be depicted as archetypical patterns of institutional attributes. Moreover, the results reveal success factors that enabled actors to prevent, alleviate or overcome specific institutional deficits in climate adaptation. Based on this, a set of diagnostic questions is provided for future in-depth institutional analyses of adaptation. Enhancing our capacities to diagnose causes of maladaptation, adaptation barriers and limits is crucial so as to device governance arrangements that match the features of specific adaptation problems.
Keywords: 330; Institutional Diagnostics; Climate Adaptation; Archetypes; Europe; Meta-Analysis